Potential Biomarkers for NSAID-Exacerbated Respiratory Disease - Hanki Park; Youngwoo Choi; Chang-Gyu Jung; Hae-Sim Park (Mediators of Inflammation)
Asthma is a common chronic disease with several variant phenotypes and endotypes. NSAID-exacerbated respiratory disease (NERD) is one such endotype characterized by asthma, chronic rhinosinusitis (CRS) with nasal polyps, and hypersensitivity to aspirin/cyclooxygenase-1 inhibitors. NERD is more associated with severe asthma than other asthma phenotypes. Regarding diagnosis, aspirin challenge tests via the oral or bronchial route are a standard diagnostic method; reliable in vitro diagnostic tests are not available. Recent studies have reported various biomarkers of phenotype, diagnosis, and prognosis. In this review, we summarized the known potential biomarkers of NERD that are distinct from those of aspirin-tolerant asthma. We also provided an overview of the different NERD subgroups.